Penguatan UMKM Melalui Pembuatan Merek Dagang dan Label pada UMKM Jajanan Camilan di Desa Joresan Mlarak Ponorogo - Husna Ni'matul Ulya; Ravina Putri Agustin (Institut Agama Islam Negeri Ponorogo, 2022)
Micro Small Medium Enterprises (MSMEs) are the most strategic national economic sectors and concern the lives of many people, so MSMEs can become the backbone of the national economy. Small and Medium Micro Enterprises (MSMEs) are also sectors that absorb the workforce and can improve community welfare. The existence of small and medium micro-businesses (MSMEs) in Joresan village itself is one of the supporting factors for the community's economy. This is because MSMEs are efforts that have never disappeared along with the development of the times. In this pandemic, the social restriction was proclaimed by the government to cut the Covid-19 distribution chain could cause a decrease in income for the MSMEs. By using the ABCD approach, the authors take steps that include inculturation, discovery, design, define, and reflection. Departing from the problem, the author was interested in taking the economic aspects as the DDR KPM program in Joresan Village. With the reinforcement of MSMEs through the manufacture of trademarks, product label repairs and help the production process for light shackles and help free marketing for products/services by collaborating with KPM DDR participants from Joresan Village and Karang Taruna Karsa Joresan Village. From the results of the implementation of the program, light snack products have increased in production. While in the implementation of an online marketing program, it has succeeded in introducing Joresan Village products/services.